2013
DOI: 10.1111/dmcn.12085
|View full text |Cite
|
Sign up to set email alerts
|

Rett syndrome: an eye‐tracking study of attention and recognition memory

Abstract: Aim The aim of this study was to examine attention and recognition memory for faces and patterns in Rett syndrome, a severely disabling neurodevelopmental disorder caused by mutations in the X‐linked MECP2 gene. Method Because Rett syndrome impairs speech and hand use, precluding most neuropsychological testing, the visual paired‐comparison paradigm (VPC) was used, together with eye tracking. In the VPC, two identical stimuli are presented for familiarization. On test, the familiar stimulus and a new one are p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 31 publications
2
54
0
2
Order By: Relevance
“…RTT is marked by arrested development of visual processing (33), atypical visually evoked cortical responses (34,35), deficits in visual attention and recognition, and unusual gaze intensity (36). In primary visual cortex (V1), "simple" stimuli, such as oriented gratings, and "complex" stimuli, such as natural scenes, activate local and distributed circuits that lead to well-defined responses from visual cortex neurons (37)(38)(39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…RTT is marked by arrested development of visual processing (33), atypical visually evoked cortical responses (34,35), deficits in visual attention and recognition, and unusual gaze intensity (36). In primary visual cortex (V1), "simple" stimuli, such as oriented gratings, and "complex" stimuli, such as natural scenes, activate local and distributed circuits that lead to well-defined responses from visual cortex neurons (37)(38)(39)(40)(41).…”
Section: Significancementioning
confidence: 99%
“…Human-computer interaction, virtual and augmented reality, usability tests, e-learning, assistive technology, pilot training assistance are some of the many eye-tracking applications [8]. Medicine, psychology and neuroscience can also benefit from this technology in studies, accessing cognitive abilities, attention and recognition memory in patients [9]. Assistive technology has been helping individuals with disabilities to improve their functional capabilities, enabling them to perform activities conducted by eye movements.…”
Section: Applications Of Eye Tracking Technologymentioning
confidence: 99%
“…This approach is of potentially great interest but may not avoid some important biases. Rose et al . have addressed these to evaluate attention as well as face and pattern recognition in a group of patients with Rett syndrome.…”
mentioning
confidence: 99%
“…Phenotypic Plasticity and the PACE Paradigm Bernard Dan et al 53 approach is of potentially great interest but may not avoid some important biases. Rose et al 20 have addressed these to evaluate attention as well as face and pattern recognition in a group of patients with Rett syndrome. They concluded that attention was 'less mature', with fewer and longer fixations, and restricted gaze focus tending to ignore nose and mouth.…”
mentioning
confidence: 99%